MEKANISME CONFIDENCE BUILDING MEASURES DAN PREVENTIVE DIPLOMACY ASEAN MARITIME FORUM (AMF) DALAM MENGATASI AKSI TERORISME DAN PEMBAJAKAN DI LAUT SULU-LAUT SULAWESI TAHUN 2015-2020 - Rena Dwi Astuti, (2022)
Along with the increasing acts of terrorism and maritime piracy in the waters of Sulu-Sulawesi in 2016, ASEAN, as a regional organization, has also responded. Moreover, the water area is a vital route for Southeast Asia. This is because, apart from having potential economic resources for the two bordering countries, Indonesia and the Philippines, the Sulu Sea-Sulawesi Sea is also an alternative route for large cargo ships that cannot pass through the Malacca Strait due to the weight of the cargo or the geographical condition of the strait which is at risk of being fatal. for your safety. This study aims to determine the mechanism of Confidence Building Measures (CBM) and Preventive Diplomacy (PD) from the ASEAN Maritime Forum (AMF) in overcoming acts of terrorism and sea piracy in the waters of Sulu-Sulawesi by using the range from 2015 to 2020. By using the concept of transnational crime. and maritime security, and international regime theory. The researcher also uses the descriptive analytical-qualitative method by using primary and secondary data sources. The results showed that the CBM and PD of AMF were in line with the principles and indicators of CBM which included information declarations, communication procedures, observation and observation activities, and stabilization efforts. Although it has not been able to fully contribute, the AMF cooperation measures have fulfilled the CBM indicators in various programs and activities.